Caractérisation phénotypique et génétique du riz africain (Oryza glaberrima Steud) phenotypic and genetic characterization of african rice (oryza glaberrima steud) - Gnacadja, C.; Berthouly-Salazar, C.; Nourou Sall, S.N.; Zekraoui, L.; Sabot, François; Pegalepo, E.; Manneh, B.; Vieira-Dalode, G.; Moreira, J.; Soumanou, M.M.; Azokpota, P.; Sie, M. (International Journal Of Advanced Research, 2018)
The agronomic interest of African rice and the morphological similarities with other species, arouse the necessity to characterize African rice for recovery and conservation. The present study aims primarily to characterize phenotypically and genetically African rice for better exploitation in aid of rice producers and consumers. Indeed, the phenotypic characteristics of the rice accessions examined have been determined in two agronomics systems (upland and irrigated) carried out about 235 accessions of African rice; and afterwards, genetic characterization using a specific marker has been carried. At the end of the analyzes, with regard to the phenotypic characters, 22 O.sativa or interspecific accessions differing morphologically on several descriptors were identified. Genetically, out of 19 profiles revealed on a 935-bp band, 14 confirmed the phenotypic results. This study shows that 221 out of 235 accessions are O. glaberrima rice. These results show that the accessions of different species analyzed were confused during the collection. They also seems to validate the possibility of hybridization between the two rice species in peasant environment. The accessions characterized strengthen the conservation effort of African rice. This collection can be used for future studies, particularly with perspective to selection and running African rice with the possibility to establish a genetic model to facilitate the transfer of useful genes from O.glaberrima to O.sativa, while controlling the reproductive barrier. Thus, it will be easy to better exploit the genetic diversity of the African species of cultivated rice.